Optical properties of Carbon quantum dots for AI enhanced flexible bioelectronics and nanomedicine - Gizachew Diga Milki (International Journal of Photochemistry and Photochemical Research, 2025)
Carbon nanodots are the emerging nanomaterials of 20 th century. Carbon nanodots is the family of carbon based material with distinguished bio-physical properties. In this paper, the optical properties of carbon nanodots are presented. One of the developments Nanoscale physics and nanotechnology is the ability of converting optical signals into meaning full information. This innovation is accelerated and improved by incorporating nanoscale materials including carbon quantum dot, carbon nanotube, and graphene quantum dots due to their pronounced optical properties. These properties enable generation of electrical signal in device such as optoelectronics, photodiodes, photoconductors, and photo detectors. Moreover, the effect of doping and AI on improving the optical properties of carbon quantum dot is visualized. This research therefore, presents the optical properties and role of carbon quantum dots as nanoelectronics and nanomedicine. In this regard, emphasis is given to the essentials of carbon quantum dot in fluorescent electronic devices, flexible electronics, and optoelectronics, power electronics, bioelectronics, and biomedicine.
Keywords: Emerging technology; Green nanotechnology; Nano polymers; Nanocomposite; green hydrogen